Contract Farming in India prospects and limitations - Prasad, Naresh; Singh, A K; Saini, J M (Indian Farming, 2018)
India is blessed with diverse agro climatic conditions which is best suited for a large number of crops. This advantage gives an edge in terms of price and hence a distinct competitive advantage. Contract farming offers one possible solution to establish an agrarian economy that ensures food and nutrition security to a population of over a billion, raw material for its expanding industrial base, surplus for export, and a fair and equitable reward system for the farming community. Contract farming is no doubt a viable alternative farming model, which provide assured and reliable input service to farmers and desired farm produce to the contracting firms. A key feature of contract farming is that it facilitates backward and forward market linkages that are the cornerstone of market-led, commercial agriculture. Well managed contract farming is considered as an effective approach to help solve many of the market linkage and access problems for small farmers.